Resepsi Al-Qur’an dan Akulturasi Budaya dalam Tradisi Yasin Hajat: Studi Living Qur’an di Pondok Pesantren Raudlatul Jannah Gemolong, Sragen - Aqiel Azkiya', Ahmad; Rohman, Miftahu; Khabib Imdad, Muhamad (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2025)
This study aims to examine the relationship between religion and culture within the Yasin Hajat recitation tradition at Raudlatul Jannah Al-Jamiliyyah Islamic Boarding School, Sragen, as a medium based of cultural da'wah. A qualitative approach was employed using a case study design through participant observation, in-depth interviews, and documentation. The findings reveal that this tradition not only represents a form of religious expression but also embodies the symbolization of sacralized local cultural values. The Yasin Hajat tradition, practiced through the repetition of specific verses for supplication, serves as an acculturative bridge between sacred texts and cultural practices. This phenomenon reinforces the concepts of living Qur’an and living hadith, positioning the tradition as a means of cultivating religiosity, social solidarity, and the contextual transmission of da'wah values. The study demonstrates that culturally adaptive da'wah can effectively bridge the gap between religion and the social life of the community.